Zincation of 4, 4-dimethyloxazoline using TMPZnCl·LiCl. A new preparation of 2-aryloxazolines. Issue 29 (13th March 2015) - Haas, Diana; Hofmayer, Maximilian S.; Bresser, Tomke; Knochel, Paul
Abstract : 4, 4-Dimethyloxazoline is directly zincated using TMPZnCl·LiCl and further functionalized by Pd-catalyzed cross-couplings, as well as Cu-mediated acylation and allylation reactions. Abstract : The metalation of 4, 4-dimethyloxazoline using TMPZnCl·LiCl provides a stable 2-zincated oxazolinyl reagent which readily undergoes palladium-catalyzed Negishi cross-couplings allowing a new access to 2-aryloxazolines. Cu-mediated acylation and allylation reactions also proceed in good yields.